(untitled) (Research, Society and Development, 2021)
The productivity of aquatic organisms and higher concentration of suspended solids that occur in areas flooded by Whitewater Rivers and the presence of aquatic macrophytes are conducive to the initial development of matrinxã (Brycon amazonicus). The objective of this study was to evaluate whether turbid waters and refuges with aquatic macrophytes improve the survival and growth of the larvae of Brycon amazonicus, a species of great interest in Amazonian fish farming. For this, two experiments were conducted using a completely randomized design and with four replicas per treatment up to 120 hours after hatching (HAH), In experiment I: Brycon amazonicus larvae at 24 HAH were subjected to three treatments with different types of water: clear water (CW); clayey water (AW) and green water (GW). Experiment II: larvae with 24 HAH were maintained in clear water (CW); clear water with refuge (CWR); green water (GW); green water with refuge (GWR); clayey water (AW) and clayey water with refuge (AWR). Experiment I showed that clayey water, followed by green water, increased the survival of larvae (73.92 and 54.32%). Growth was best in larvae maintained in green water. In experiment II, the use of aquatic macrophytes did not influence the survival and growth of the larvae. Thus, we suggest the use of turbid (clayey and green) waters without refuge to increase the survival and growth of Brycon amazonicus larvae.